Exposure of Fexofenadine, but Not Pseudoephedrine, Is Markedly Decreased by Green Tea Extract in Healthy Volunteers. Issue 3 (29th June 2022) - Misaka, Shingen; Ono, Yuko; Taudte, R. Verena; Hoier, Eva; Ogata, Hiroshi; Ono, Tomoyuki; König, Jörg; Watanabe, Hiroshi; Fromm, Martin F.; Shimomura, Kenju
Abstract : Green tea (GT) alters the disposition of a number of drugs, such as nadolol and lisinopril. However, it is unknown whether GT affects disposition of hydrophilic anti‐allergic drugs. The purpose of this study was to investigate whether pharmacokinetics of fexofenadine and pseudoephedrine are affected by catechins, major GT components. A randomized, open, 2‐phase crossover study was conducted in 10 healthy Japanese volunteers. After overnight fasting, subjects were simultaneously administered fexofenadine (60 mg) and pseudoephedrine (120 mg) with an aqueous solution of green tea extract (GTE) containing (−)‐epigallocatechin gallate (EGCG) of ~ 300 mg or water (control). In vitro transport assays were performed using HEK293 cells stably expressing organic anion transporting polypeptide (OATP)1A2 to evaluate the inhibitory effect of EGCG on OATP1A2‐mediated fexofenadine transport. In the GTE phase, the area under the plasma concentration‐time curve and the amount excreted unchanged into urine for 24 hours of fexofenadine were significantly decreased by 70% ( P  < 0.001) and 67% ( P  < 0.001), respectively, compared with control. There were no differences in time to maximum plasma concentration and the elimination half‐life of fexofenadine between phases. Fexofenadine was confirmed to be a substrate of OATP1A2, and EGCG (100 and 1, 000 μM) and GTE (0.1 and 1 mg/mL) inhibited OATP1A2‐mediated uptake of fexofenadine. On the contrary, the concomitant administration of GTE did not influence the pharmacokinetics of pseudoephedrine. These results suggest that intake of GT may result in a markedly reduced exposure of fexofenadine, but not of pseudoephedrine, putatively by inhibiting OATP1A2‐mediated intestinal absorption.